Facile synthesis of FeCo alloys encapsulated in nitrogen-doped graphite/carbon nanotube hybrids: efficient bi-functional electrocatalysts for oxygen and hydrogen evolution reactions. (2nd February 2018) - Du, Bing; Meng, Qing-Ting; Sha, Jing-Quan; Li, Ji-Sen
Abstract : Novel FeCo alloys encapsulated in nitrogen-doped graphite/carbon nanotube composite based on MOFs was firstly obtained. Impressively, the hybrid demonstrates the outstanding electrocatalytic performance for the oxygen and hydrogen evolution reaction. Abstract : The development of highly efficient and durable non-noble metal catalysts for full water splitting has attracted tremendous attention in recent years. Herein, for the first time, we present a facile synthesis of FeCo alloys encapsulated in a nitrogen-doped graphite/carbon nanotube (FeCo@NG/NCNT) hybrid using MOFs as precursors. Impressively, due to the synergistic interplay between FeCo alloys and NG/NCNTs, the resultant hybrid as a bi-functional electrocatalyst demonstrates an outstanding electrocatalytic performance for both oxygen and hydrogen evolution reactions in alkaline electrolytes. Most importantly, this work paves a new route in rationally designing and developing high-efficienct and stable bifunctional electrocatalysts for overall water splitting.